Diagnostic lymph node extirpation in CUP syndrome – useful or damaging?. (3rd October 2018) - Wirth, Markus; Pigorsch, Steffi; Strassen, Ulrich; Johnson, Felix; Pickhard, Anja; Wirth, Magdalena
Abstract: Objective: In a proportion of patients with cervical lymph node metastasis no primary can be found even with modern imaging and careful clinical examination (cancer of unknown primary syndrome = CUP syndrome). The ideal diagnostic approach is still debated on. Methods: The clinical data of 75 patients (median age: 61.8 years; 16 females and 59 males), which have been treated for cervical squamous cell carcinoma of unknown primary syndrome in our hospital were retrospectively analyzed. Results: In 12% of patients ( n  = 9) the primary demarcated in a time period of up to 5.3 years after diagnosis. In the patients who did not receive adjuvant radiotherapy ( n  = 13), primary became apparent in 38%. Diagnostic lymph node extirpation delayed time until therapeutic neck dissection on average for 3 weeks. In 62% of patients with previous lymph node extirpation (pN2a–N2c), a modified radical neck dissection was required compared to 41% when the surgical site was not operated on. Conclusions: In 12% of patients' primary demarcated in the course of the disease. A diagnostic lymph node extirpation was compared to direct therapeutic neck dissection after frozen section analysis associated with a three weeks delayed therapy and higher rate of modified radical neck dissection.